Interactive Powerpoint-Based Educational Games: Media to Stimulate Group B Children's Language Skills - Satyadewi, Ni Putu Ayu; Ambara, Didith Pramunditya; Wiarta, I Wayan (Universitas Pendidikan Ganesha, 2024)
Children have difficulty developing language because the learning process is still centered on the teacher and the child's lack of concentration. This research aims to develop educational game media using interactive PowerPoint on the insect sub-theme. This type of research is development research using the ADDIE model. The subjects of this research were each a design expert, content/materials expert, instructional design expert, and media expert. There are also individual test subjects, small group test subjects, and product effectiveness subjects. The data collected is quantitative data using questionnaire and observation methods. The data analysis techniques used are quantitative descriptive analysis and inferential statistics. The results of expert tests sequentially obtained results, namely product design scored 90.90% with very good qualifications, media content 96.67% with very good qualifications, instructional design 93.75% with very good qualifications, and learning media 95% with very good qualifications. Product trials on subjects included individual testing which obtained a score of 95% with very good qualifications and small group testing obtained a score of 94.17% with very good qualifications. The results of the effectiveness test show that t-count > t-table (8.878 > 1.761), so there is a significant influence. This means that it is known that the new interactive PowerPoint-based educational game media is suitable and effective for PAUD children, and is able to stimulate children's language skills. The implications of this research include increasing attractiveness and interactivity in learning, thereby providing a more interesting learning experience.